Lessons from the Nipah virus outbreak in Malaysia. - Looi, Lai Meng; Chua, Kaw Bing (College of Pathologists, Academy of Medicine Malaysia, 2007)
The Nipah virus outbreak in Malaysia (September 1998 to May 1999) resulted in 265 cases of acute encephalitis with 105 deaths, and near collapse of the billion-dollar pig-farming industry. Because it was initially attributed to Japanese encephalitis, early control measures were ineffective, and the outbreak spread to other parts of Malaysia and nearby Singapore. The isolation of the novel aetiological agent, the Nipah virus (NiV), from the cerebrospinal fluid of an outbreak victim was the turning point which led to outbreak control 2 months later. Together with the Hendra virus, NiV is now recognised as a new genus, Henipavirus (Hendra + Nipah), in the Paramyxoviridae family. Efforts of the local and international scientific community have since elucidated the epidemiology, clinico-pathophysiology and pathogenesis of this new disease. Humans contracted the infection from close contact with infected pigs, and formed the basis for pig-culling that eventually stopped the outbreak. NiV targeted medium-sized and small blood vessels resulting in endothelial multinucleated syncytia and fibrinoid necrosis. Autopsies revealed disseminated cerebral microinfarctions resulting from vasculitis-induced thrombosis and direct neuronal involvement. The discovery of NiV in the urine and saliva of Malaysian Island flying foxes (Pteropus hypomelanus and Petropus vampyrus) implicated these as natural reservoir hosts of NiV. It is probable that initial transmission of NiV from bats to pigs occurred in late 1997/early 1998 through contamination of pig swill by bat excretions, as a result of migration of these forest fruitbats to cultivated orchards and pig-farms, driven by fruiting failure of forest trees during the El Nino-related drought and anthropogenic fires in Indonesia in 1997-1998. This outbreak emphasizes the need for sharing information of any unusual illnesses in animals and humans, an open-minded approach and close collaboration and co-ordination between the medical profession, veterinarians and wildlife specialists in the investigation of such illnesses. Environmental mismanagement (such as deforestation and haze) has far-reaching effects, including encroachment of wildlife into human habitats and the introduction of zoonotic infections into domestic animals and humans.